Regulation of R1 Plasmid Transfer by H-NS, ArcA, TraJ, and DNA Sequence Elements - Bischof, Karin; Schiffer, Doris; Trunk, Sarah; Höfler, Thomas; Hopfer, Anja; Rechberger, Gerald; Koraimann, Günther (Frontiers in Microbiology, 2020)
In conjugative elements such as ICEs or conjugative plasmids transcription of DNA transfer genes is a prerequisite for cells to become transfer competent, i.e. capable of delivering plasmid DNA via bacterial conjugation into new host bacteria. In the large family of F-like plasmids belonging to the MobF12A group, transcription of DNA transfer genes is tightly controlled and dependent on the activation of a single promoter, designated PY. Plasmid encoded TraJ and chromosomally encoded ArcA proteins are known activators, whereas the nucleoid associated protein H-NS silences the PY promoter. To better understand the role of these proteins in PY promoter activation we performed in vitro DNA binding studies using purified H-NS, ArcA and TraJR1 (TraJ encoded by the conjugative resistance plasmid R1). All proteins could bind to R1PY DNA with high affinities, however, only ArcA was found to be highly sequence specific. DNase I footprinting studies revealed three H-NS binding sites, confirmed the binding site for ArcA and suggested that TraJ contacts a dyad symmetry DNA sequence located between -51 and -38 in the R1PY promoter region. Moreover, TraJR1 and ArcA supplied together changed the H-NS specific protection pattern suggesting that these proteins are able to replace H-NS from R1PY regions proximal to the transcription start site. Our findings were corroborated by PY-lacZ reporter fusions with a series of site specific R1PY promoter mutations. Sequential changes of some critical DNA bases in the TraJ binding site (jbs) from plasmid R1 to plasmid F led to a remarkable specificity switch: The PY promoter became activatable by F encoded TraJ whereas TraJR1 lost its activation function. The R1PY mutagenesis approach also confirmed the requirement for the host-encoded response-regulator ArcA and indicated that the sequence context, especially in the -35 region is critical for PY regulation and function.